"They say 'yes, I'm doing it… .and I'm fine' ": the lived experience of supporting teenagers who misuse drugs. Issue 2 (3rd April 2021) - Maynard, Emma; Pycroft, Aaron; Spiers, Johanna
ABSTRACT: We present an original phenomenological study conducted with a local authority Early Help and Prevention social care team, in which we investigated the lived experience of parents and practitioners of young people who misuse drugs amid a practice agenda focused on harm reduction. Our findings reflect practitioners' lived experience of direct work with young people and parents, and parents' approach to their risk-taking children. Our data identifies key concerns reflecting wider social discourse surrounding young people, in particular; the juxtaposition of adolescents as both vulnerable children, and agentic risk-takers, in the context of children's rights, and the role of adults in young lives. Our findings indicate a complex position amid multifactorial needs, risk, and offending behaviour, and reveals tensions between professionally driven harm reduction approaches, versus parents' attempts to control and protect their children, and highlight the complex transition made may protective adults as agentic adolescents forge their life chances.